Technoeconomics of sugar cane bagasse valorization to lactic acid using pinch technology: distillation vs reactive distillation - Maity, Sunil K.; Agrawal, Deepti; Gadkari, Siddharth; Vanapalli, Kumar Raja; Yong, Yang-Chun; Zhu, Daochen; Chen, Chang; Kumar, Vinod (American Chemical Society, 2025)
Sugar cane is one of the largest agricultural crops, and sugar cane bagasse (SCB), a major waste from sugar cane processing, is an abundant and inexpensive source of fermentable sugars for producing diverse platform chemicals. The present study evaluates the technoeconomic viability of L (+) lactic acid (LA) production from SCB with different stand-alone process scenarios modeled using the pinch method. It critically evaluates various cost-contributing factors when a sugar-rich hydrolysate is obtained via two different pretreatment methods: dilute acid and alkali. The cost-benefit of LA purification by conventional distillation (CD) is further compared to reactive distillation (RD). The pinch method cuts the LA manufacturing costs by 10-11%. Alkali pretreatment combined with RD involves a lower capital investment and utility consumption than the CD counterpart and slightly less LA manufacturing cost. However, LA production via dilute acid pretreatment and purification by RD emerges as the most profitable scenario due to capital investment, utility demand, and chemical consumption savings. This scenario offers the minimum LA selling price of 2.3 US$/kg for an 8.5% discount factor and a 5 year payback period. However, for a 20 year plant life and 2.5 US$/kg factory-gate LA selling price, the internal rate of return was 31% and the payback period was 4.4 years for an 8.5% discount factor.
Keywords: lactic acid; sugar cane bagasse; process modeling; pinch analysis; reactive distillation; 40 Engineering; 34 Chemical Sciences; 3401 Analytical chemistry; 4004 Chemical engineering